2001
DOI: 10.1002/jemt.1102
|View full text |Cite
|
Sign up to set email alerts
|

Classic NSAID and selective cyclooxygenase (COX)‐1 and COX‐2 inhibitors in healing of chronic gastric ulcers

Abstract: Prostaglandins (PG) derived from COX-1 are essential for the maintenance of mucosal integrity but COX-2 isoform synthesizes PG at a site of inflammation. Recently, COX-2 mRNA expression was demonstrated at the ulcer edge during healing of chronic gastric ulcers but the role for expression of COX-2 and its products such as PGE(2) and cytokines including interleukin (IL-1beta) and tumor necrosis factor alpha (TNFalpha) in ulcer healing remains unknown. In this study, Wistar rats with gastric ulcers produced by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 33 publications
4
71
1
4
Order By: Relevance
“…40) While COX-2 is not constitutively expressed in most of the tissues but is dramatically up-regulated during inflammation and injury. 41) In our study, exposure to ethanol produced a significant fall in PGE 2 production in the gastric mucosa despite overexpression of COX-1 and COX-2. This result might be explained by other reports described that in the presents of oxidative damage, the PGs could be converted into products of oxidation such as 8-iso-PGF 2 alpha.…”
Section: Discussionsupporting
confidence: 46%
“…40) While COX-2 is not constitutively expressed in most of the tissues but is dramatically up-regulated during inflammation and injury. 41) In our study, exposure to ethanol produced a significant fall in PGE 2 production in the gastric mucosa despite overexpression of COX-1 and COX-2. This result might be explained by other reports described that in the presents of oxidative damage, the PGs could be converted into products of oxidation such as 8-iso-PGF 2 alpha.…”
Section: Discussionsupporting
confidence: 46%
“…Administration of NS-398 alone does not induce gastric lesions in drug-treated animals (Tomisato et al, 2004); however, this drug has been shown to delay ulcer healing (Brzozowski et al, 2001;Peskar et al, 2001). We have shown previously that chronic exposure (72 h) to 100 M NS-398 decreases cell migration in wounded intestinal epithelial monolayers (Freeman et al, 2007), and others have shown comparable inhibition of re-epithelialization of wounded gastric epithelial cell monolayers (Pai et al, 2001).…”
Section: Methodsmentioning
confidence: 88%
“…Shen 59) reported that NS-398 significantly delayed the healing of acetic acid ulcers in rats, possibly by suppressing increases in PG levels in the ulcerated gastric mucosa. Brzozowski et al 60) discovered that both aspirin and indomethacin significantly delay ulcer healing due to suppression of endogenous PG, impairment of gastric mucosal blood flow at the ulcer site, and excessive cytokine expression (IL-1b, TNF a) and release. Similar results were obtained with highly selective COX-1 (resveratrol) and COX-2 inhibitors (NS-398), suggesting that both COX isomers are important sources of PG that contribute to ulcer healing.…”
Section: Cox-2 and Paf Inhibitors And Plateletsmentioning
confidence: 99%
“…It should be noted that the inhibitory effect of NS-398 was weaker than that of indomethacin. 148) In addition, Guo et al 149) also demonstrated that rofecoxib, a highly selective COX-2 inhibitor, significantly increased the size of acetic acid ulcers in rats and decreased the amount of microvasculature, bFGF protein expression, and PGE 2 levels. In our laboratory, the effects of p38, a MAP-kinase family compound, on the healing of acetic acid ulcers were examined in rats.…”
Section: Epithelial Regeneration and Mucus Secretionmentioning
confidence: 99%